HUBUNGAN PENGELOLAAN WORKSHOP BANGUNAN DENGAN HASIL BELAJAR SISWA PADA MATA DIKLAT PRAKTEK KERJA KAYU JURUSAN TEKNIK BANGUNAN SMK N 2 SAWAHLUNTO TAHUN 2013/2014 - 502-507 , Ferdi Kurnia (Universitas Negeri Padang, 2014)
Abstract This research is motivated by the lack of students’ learning outcomes at Building Engineering Department of SMK N 2 Sawahlunto. This research has goal to determine if there is relationship or not between building management workshop and students’ learning outcomes in practice wood at Building Engineering Department of SMK N 2 Sawahlunto. Design of this research is a descriptive correlational. The population of this research is all of the students in the faculty of building engineering, 2013/2014 school year totaled 36 people. Sample was taken from all members of the population who called Total Sampling and the number of samples are 36 students. Independent variable of this research is Workshop Management and dependent variable of this research is Learning Outcomes of Wood Practice. Based on the result of correlation analysis is obtained r value 0.743, correlation coefficient r is bigger than r Table (0.743> 0.329). It can be concluded, there is a relationship between workshop management and students’ learning outcomes in Wood Practice at Building Engineering Department of SMKN 2 Sawahlunto on sufficient category, the level of the relationship is between 0.6 to 0.8. Key words : Relationship, Workshop Management, Learning Outcomes.